1986
DOI: 10.1139/o86-018
|View full text |Cite
|
Sign up to set email alerts
|

An immunochemical study of Neurospora nucleases

Abstract: Nucleases derived from Neurospora crassa mycelia with neutral single-strand (ss) endodeoxyribonuclease activity have been examined by immunochemical techniques and by sodium dodecyl sulfate - DNA gel electrophoresis. All of the intracellular nucleases, which have different divalent metal ion requirements, different strand specificities with single- and double-strand DNA, different modes of action on DNA and RNA, and other distinguishing characteristics, are immunochemically related to Neurospora endo-exonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Several extracellular phosphatases have been characterized, including the PHO-3 repressible acid phosphatase and the PHO-2 repressible alkaline phosphatase. Two secreted phosphate-repressible alkaline DNases have been described (394), as well as a DNase A and a singlestrand-specific endonuclease (250). There are more than 30 nucleases and phosphatases in the Neurospora genome.…”
Section: Extracellular Digestionmentioning
confidence: 99%
“…Several extracellular phosphatases have been characterized, including the PHO-3 repressible acid phosphatase and the PHO-2 repressible alkaline phosphatase. Two secreted phosphate-repressible alkaline DNases have been described (394), as well as a DNase A and a singlestrand-specific endonuclease (250). There are more than 30 nucleases and phosphatases in the Neurospora genome.…”
Section: Extracellular Digestionmentioning
confidence: 99%
“…From mitochondria, a strand non-speci¢c endonuclease [11] and a ssDNA binding endo^exonuclease not inhibited by ATP [24] have also been isolated. Fraser et al [93] demonstrated by immunochemical techniques that all the above enzymes from N. crassa are derived from one or more related large inactive (precursor) polypeptides which undergo proteolysis to produce various active forms of nucleases. This inactive precursor was shown to have a M r of 93^95 kDa [94].…”
Section: Puri¢cationmentioning
confidence: 99%
“…This inactive precursor was shown to have a M r of 93^95 kDa [94]. Additionally, Fraser et al [93] showed that endo^exonucleases from A. nidulans and S. cerevisiae are immunologically related to N. crassa endoê xonuclease but not to single-strand-speci¢c nucleases like S1, P1 and mung bean nuclease. Similarly, isoforms of the nucleases were observed in S. aureus [95], B. subtilis [25], A. espejiana [12], S. marcescens kums 3958 [23], tobacco pollen [43], P. hybrida pollen [45] and S. marcescens [969 8].…”
Section: Puri¢cationmentioning
confidence: 99%
“…The antibodies raised previously to the purified Neurospora endo-exonuclease were shown to cross-react not only with the nuclear and mitochondrial endo-exonuclease of S. cerevisiae described above but also with an intracellular endo-exonuclease of Aspergillus nidulans (H. Koa, M. J. Fraser, and E. Kafer, unpublished observations) and with a mitochondrial nuclease of mouse plasmacytoma cells (18). However, no immunochemical cross-reaction was seen with other fungal and plant nucleases with sugar-nonspecific but single-strand-specific endonuclease activities, such as the Si nuclease of Aspergilluls oryzae, the P1 nuclease of Penicillium citrinum, and mung bean nuclease, and also not with a number of DNases tested (11). Thus, the nuclear and mitochondrial sugar-nonspecific endo-exonuclease in eucaryotes may constitute a separate class of nucleases.…”
mentioning
confidence: 97%